Income Assessment of Beef Cattle Farming and Measurement of The Customer Satisfaction Index (CSI) on Farmer's Satisfaction Level - Syastiawan, Andi; Siregar, Ahmad Ramadhan; Sirajuddin, Sitti Nurani; Dambe, Jumriani (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
This study evaluated cattle farmer’s satisfaction with government support programs and compared incomes between farmers using artificial insemination (AI) and natural breeding in Liliriaja District, South Sulawesi. Using a quantitative descriptive approach, data were collected through structured questionnaires and interviews with 150 purposively selected cattle farmers. The Customer Satisfaction Index (CSI) method assessed four main indicators: technical service quality, IB availability, income generation, and production yield. The results showed a moderate level of satisfaction (CSI = 73.78%), with the highest score for AI availability (WS = 1.089) due to its critical role in genetic improvement. However, the income support program had the lowest satisfaction (WS = 0.621), highlighting gaps in subsidy accessibility and market linkages. Economically, IB calves generated higher income (IDR 8,500,000/head) compared to natural mating (IDR 6,500,000/head), despite IB requiring higher feed costs. This study underscores the need for policy improvements, including reviving subsidy programs, technical training, and optimal implementation of IB to improve farmers' welfare and sustainable livestock productivity.